European cooperation between tax, customs and judicial authorities : the Netherlands, England and Wales, France and Germany - Vervaele, J. A. E. (Kluwer Law International The HagueNL, 2002)
Deals with the cooperation between Member States of the European Union in their fight against fraud. Examines and compares the law of four jurisdictions within the European Union.